2015
DOI: 10.1021/jp5055414
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the Catalytic Activity of Copper in the Cycloaddition of Azide and Alkynes (CuAAC) with the Topology of2ρ(r) and∇∇2ρ(r)

Abstract: The distinct role of the Cu(I) in the Huisgen dipolar cycloaddition of azides to alkynes (denoted as CuAAC) is disclosed by following the evolution of the topology of the Laplacian of the electronic charge density, ∇(2)ρ(r), and its gradient vector field, ∇∇(2)ρ(r), along the reaction coordinate with several density functionals (wB97XD, LCwPBE, M06-2X, M06-L, B3LYP) and the 6-311++G(d,p) basis set. Remarkably, in view of the topology of ∇(2)ρ(r) and ∇∇(2)ρ(r), the mechanism appears to be diverse (asynchronous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 102 publications
1
28
0
Order By: Relevance
“…Following these pioneering computational works, several theoretical mechanistic investigations on the CuAAC reactions have been carried out, considering various copper systems, most of them multinuclear, and leading basically to similar qualitative conclusions [34,[58][59][60][61][62]. A recent investigation pointed out the possibility for a concerted vs. stepwise nature of the mechanism, however, depending on the ligand nature [63]. The most recent experimental mechanistic study by Fokin's group unambiguously demonstrated the participation of a dinuclear copper intermediate in the case of a CuAAC reaction in which a mixture of Cu(I)(aryl) complex and [Cu(I)(MeCN) 4 ] + were used ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Following these pioneering computational works, several theoretical mechanistic investigations on the CuAAC reactions have been carried out, considering various copper systems, most of them multinuclear, and leading basically to similar qualitative conclusions [34,[58][59][60][61][62]. A recent investigation pointed out the possibility for a concerted vs. stepwise nature of the mechanism, however, depending on the ligand nature [63]. The most recent experimental mechanistic study by Fokin's group unambiguously demonstrated the participation of a dinuclear copper intermediate in the case of a CuAAC reaction in which a mixture of Cu(I)(aryl) complex and [Cu(I)(MeCN) 4 ] + were used ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Originally,the catalytic process has been proposed to proceed via amechanism that involves ametallacyclic intermediate, 7, with asingle Cu atom. [22,[25][26][27][28][29][30] It is thus conceivable that such Cu I -mediated mechanisms could bring Figure 1. [22,[25][26][27][28][29][30] It is thus conceivable that such Cu I -mediated mechanisms could bring Figure 1.…”
mentioning
confidence: 99%
“…[24] Later, reaction mechanisms involving dinuclear Cu I complexes were detected experimentally and analyzed in terms of quantum chemical calculations to elucidate the details of the thermal reaction. [22,[25][26][27][28][29][30] It is thus conceivable that such Cu I -mediated mechanisms could bring Relative energies (with respect to the optimized species as indicated in the lower-left corners)a long the intrinsic reaction coordinates (IRC) of the rate-determining step in the thermal limit (F 0 = 0nN) and optimized at constant external forces (F 0 = 1, 2, 3, and 4nN) for the reaction mechanisms P1 to P6 as sketched in Figure 1.…”
mentioning
confidence: 99%
“…[22][23][24][25][26][27][28] All the geometries including reactants, intermediates, transition states, and products were obtained at ωB97XD/def2-SVP theory level. [29][30][31] ωB97XD is range-separated functional, which can obtain satisfactory accuracy for thermochemistry, kinetics, and noncovalent interactions and be used for reaction mechanism research [32][33][34][35][36] with def2-SVP basis set. [37][38][39] The calculation used solvent model SMD, [40][41][42] and hexane was taken as the solvent.…”
Section: Computationsmentioning
confidence: 99%